2018
DOI: 10.1016/j.jss.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Trametinib prevents mesothelial-mesenchymal transition and ameliorates abdominal adhesion formation

Abstract: Cecal abrasion in mice is a reliable model to study abdominal adhesions, which can be ameliorated using the MEK1/2 inhibitor trametinib. While blocking adhesion formation at the cell and molecular levels, trametinib, at the therapeutic doses utilized, did not impair the wound healing at the laparotomy site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…JUN signals via several known fibrosis-related pathways, including VEGF , FGFR , PDGFR , and TGFBR 6 . Inhibitors of these well-known, downstream, fibrosis-associated pathways have shown some effect at modulating adhesion formation in mice, for example the MEK inhibitor trametinib 7 , but it has remained unknown what the upstream transcriptional regulator of adhesion pathology might be. Furthermore, abdominal adhesion fibroblasts have yet to be characterized at the single-cell level to appreciate the functional heterogeneity involved.…”
Section: Introductionmentioning
confidence: 99%
“…JUN signals via several known fibrosis-related pathways, including VEGF , FGFR , PDGFR , and TGFBR 6 . Inhibitors of these well-known, downstream, fibrosis-associated pathways have shown some effect at modulating adhesion formation in mice, for example the MEK inhibitor trametinib 7 , but it has remained unknown what the upstream transcriptional regulator of adhesion pathology might be. Furthermore, abdominal adhesion fibroblasts have yet to be characterized at the single-cell level to appreciate the functional heterogeneity involved.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study that examined mesenchymal cell phenotypes present in the normal and fibrotic lungs of mice identified six distinct subpopulations in normal lungs and seven distinct subpopulations in fibrotic lungs [45]. In agreement with these observations, other studies have shown that during the wound healing process, some populations of fibroblasts display certain features characteristic of activated myofibroblasts, such as increased synthesis of ECM macromolecules but remarkably, lack other important features such as α-SMA expression [46, 47].…”
Section: Introductionmentioning
confidence: 60%
“…[ 263 ] or Macarak et al. [ 264 ] The mouse models were preferred for the evaluation of drugs. Due to body size, abrasion only models were mainly reported.…”
Section: Animal Modelsmentioning
confidence: 99%